Extended intensive care correlates with worsening of surgical outcome after elective abdominal aortic reconstruction - Dovzhanskiy, Dmitriy I.; Schwab, Simone; Bischoff, Moritz; Brenner, Thorsten; Weigand, Markus A.; Hinz, Ulf; Böckler, Dittmar (The journal of cardiovascular surgery, 2021)
BACKGROUND: The aim of this study was to evaluate the impact of extended postoperative intensive care on short- and long-term patient outcome after elective abdominal aortic surgery and to assess the risk factors for patient survival after extended intensive care unit (ICU) treatment. METHODS: The data of 231 patients that underwent open or endovascular abdominal aortic surgery were retrospectively analysed with regard to extended postoperative intensive care, defined as ICU treatment for more than 24 consecutive hours. Pre- and intraoperative factors were evaluated. The endpoints of the study were postoperative complications, mortality, and long-term follow-up. Univariate and multivariate Cox proportional regression analyses were performed to identify risk factors of worse overall survival. RESULTS: Extended postoperative intensive care was needed in 84 patients (63 after open and 21 after endovascular surgery). The period of ICU treatment was similar in both groups. Only the wound complications (31.8% vs. 9.5%, P=0.0498; OR 4.42 [0.94-20.84]) and the rate of acute kidney injury (82.5% vs. 57.1%, P=0.0352; OR 3.55 [1.20-0.46]) were more frequent after open surgery, whereas brief reactive psychosis (38.1% vs. 14.3%, P=0.0281; OR 0.27 [0.09-0.84]) was more frequent after endovascular surgery. ICU stay of 28 days correlated with significantly lower survival rates compared to a shorter ICU stay (P=0.0034), independent of open or endovascular techniques. Other multivariate risk factors for worse survival were the absence of preoperative aspirin medication, a Body Mass Index (BMI) of <25, chronic renal insufficiency, and coronary artery disease. Endovascular therapy was a positive predictive factor of short ICU stay of <3 days. CONCLUSIONS: The outcome after extended intensive care following elective aortic surgery is strongly dependent on the length of ICU stay. ening of surgical outcome after elective abdominal aortic reconstruction. J Cardiovasc Surg 2021;62:591-9. DOI: 10.23736/S0021-9509.21.11842-7)